2009
DOI: 10.1371/journal.pone.0004774
|View full text |Cite
|
Sign up to set email alerts
|

Orally Available Selective Melanocortin-4 Receptor Antagonists Stimulate Food Intake and Reduce Cancer-Induced Cachexia in Mice

Abstract: BackgroundCachexia is among the most debilitating and life-threatening aspects of cancer. It represents a metabolic syndrome affecting essential functional circuits involved in the regulation of homeostasis, and includes anorexia, fat and muscle tissue wasting. The anorexigenic peptide α-MSH is believed to be crucially involved in the normal and pathologic regulation of food intake. It was speculated that blockade of its central physiological target, the melanocortin (MC)-4 receptor, might provide a promising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
44
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 29 publications
4
44
0
1
Order By: Relevance
“…The results reported from this study are well in accordance with previous studies describing robust orexigenic effects and showing that endogenous peptidic or small molecule MC4R antagonists enhance food intake in healthy animals [44,50]. Besides the experiments using SNT2007707 and SNT207858 in C26 adenocarcinoma mice performed by Weyermann [45], a number of other compounds with MC4R antagonist effects were investigated elsewhere -Chen et al [52] reported on a new compound from piperazine family, the name of which is yet to be attributed, Vos et al [53] investigated effects of ML00253764 in C26 adenocarcinoma mice, Nicholson et al [44] investigated ML00253764 in Lewis Lung carcinoma mice. Cheung et al [54] investigated effects of a MC4R antagonist called NBI-12i in rodent models of cachexia with 5/6 nephrectomy where 3 mg/kg of NBI-12i or saline was given to subtotally nephrectomized or sham-operated mice intraperitoneally, twice per day, for a period of 14 days.…”
Section: Currently Available Small-molecule Inhibitors Of MC Pathwaysupporting
confidence: 92%
See 4 more Smart Citations
“…The results reported from this study are well in accordance with previous studies describing robust orexigenic effects and showing that endogenous peptidic or small molecule MC4R antagonists enhance food intake in healthy animals [44,50]. Besides the experiments using SNT2007707 and SNT207858 in C26 adenocarcinoma mice performed by Weyermann [45], a number of other compounds with MC4R antagonist effects were investigated elsewhere -Chen et al [52] reported on a new compound from piperazine family, the name of which is yet to be attributed, Vos et al [53] investigated effects of ML00253764 in C26 adenocarcinoma mice, Nicholson et al [44] investigated ML00253764 in Lewis Lung carcinoma mice. Cheung et al [54] investigated effects of a MC4R antagonist called NBI-12i in rodent models of cachexia with 5/6 nephrectomy where 3 mg/kg of NBI-12i or saline was given to subtotally nephrectomized or sham-operated mice intraperitoneally, twice per day, for a period of 14 days.…”
Section: Currently Available Small-molecule Inhibitors Of MC Pathwaysupporting
confidence: 92%
“…The other molecule, SNT207858 is a 22 nM MC4R antagonist with a 170-fold selectivity vs. MC3R and a 40-fold selectivity versus MC5R [49,50]. In mice subcutaneously implanted with C26 adenocarcinoma cells, repeated oral administration of each of the two compounds almost completely prevented tumor induced weight loss, and diminished loss of lean body mass and fat mass thus confirming significant anti-cachexia effects of both compounds [45], whereas a single subcutaneous injection of 20 mg/kg of either SNT207707 or SNT207858 distinctly increased food intake of the mice (p < 0.001) and the amount of food taken during the four hours observation period was roughly 3-fold the amount taken by the vehicle treated controls. The results reported from this study are well in accordance with previous studies describing robust orexigenic effects and showing that endogenous peptidic or small molecule MC4R antagonists enhance food intake in healthy animals [44,50].…”
Section: Currently Available Small-molecule Inhibitors Of MC Pathwaymentioning
confidence: 99%
See 3 more Smart Citations